Elite cross-country skiers` adaptations of the diagonal stride technique at different inclinations - Goepfert, C.; Holmberg, H. C.; Müller, E.; Lindinger, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Despite the equal relevance of classic and freestyle in modern cross-country skiing, the main focus of biomechanical studies has mainly been on the latter technique. Diagonal stride [DIA] as a main classical technique has further developed over the last 20 years. There is still a lack of biomechanical data describing DIA and adaptations to different inclinations. A previous study showed that skiers increased cycle rate rather than cycle length as the strategy to adapt to increasing inclinations (Bilodeau et al. 1992). However, no kinetic or joint kinematic data were presented. The aim of the present study was to identify kinetic and kinematic adaptations in DIA at different inclinations. Methods: Twelve elite XC skiers (Swedish National Team; VO2max-DIA: 72.3 ± 3.8 ml·kg-1·min-1) performed DIA roller skiing at treadmill inclinations of 3°, 6° and 9° at 11 km·h-1 for biomechanical analyses. Leg and arm joint angles (goniometers), pole force (strain gauge), both at 2000 Hz, and plantar force (Pedar Mobile) at 100 Hz were recorded. Repeated measures ANOVA were calculated in order to examine the biomechanical differences between the named inclinations. The statistical level of significance was set at P<0.05. Results: Cycle time [CT] (P<0.01) and relative (%CT) arm recovery time (P<0.05) decreased at higher inclinations. Cycle rate and relative poling time both increased (both P<0.01). No differences were found for the relative durations of leg-ground contact and leg swing. All the force values measured were greatest at the steepest inclination, including peak pole and leg forces, forefoot force in ground position and impulses of pole and leg push-off (all P<0.01). Elbow [EA], hip [HA] and knee [KA] angle minima, EA at pole plant, KA at ski plant and HA maximum before push-off decreased (all P<0.01). The elbow extension range of motion [ROM] and knee (both P<0.01), as well as hip push-off extension ROM (P<0.05), increased with inclination. Angular push-off flexion velocity (P<0.01) decreased, along with higher angular push-off extension velocities in the ankle (P<0.05), knee and hip joints (both P<0.01) at steeper inclinations. Conclusion: Elite skiers adapt the DIA technique to increased inclinations through substantial changes in pole and leg kinetics and joint kinematics, with only minor changes in specific phase durations. Arm and leg actions show larger amplitudes, higher angular velocities, longer poling times, higher forces and impulses generated at higher frequencies. We suggest that XC skiers should use technique, endurance and strength training at different inclinations in order to train these aspects specifically.